A Study on Behaviour of Youth with Respect to Spending Money in Bangalore - Dr. S. Rajarajeswari, Dr. V. Sasikala, Nasreen Sayyed, Dr. S. Ramesh (Journal of Informatics Education and Research, 2023)
Apart from taking care of their personal and other entertainment expenses, the primary purpose of earning by women is to save for future security or unpredictable future contingencies. The factors that affect Indian women, to a large extent, is the family decisions, and only few take self-decisions. As women are emerging as the main workforce in the country and contribute significantly towards social and economic development of the country, it is very much necessary to have a study on understanding the investment behaviour of women and also how their behavior is affected by their perception of savings and how they consider various investment avenues before making investment. India is a developing nation with a middle class that has become more financially stable over time. As adults' spending power has grown, even children have become free-hand spenders and sometimes spendthrifts. The question of why, where, and how youth spend and save is addressed in this paper. The young people referred to here are between the ages of 15 and 25.The purchasing habits are also changing as a result of the expanding economy. The segment of society that is immortalized in advertisements is between the ages of 15 and 25.In contrast, this youth in India is not depicted as financially and emotionally secure in the West. The spending habits of our nation's youth are vastly different from one another. The purpose of this paper is to investigate the spending and saving habits of young people in Bangalore.